Correction: A sequential model of the contribution of preschool fluid and crystallized cognitive abilities to later school achievement. - Philippe Carpentier; Geneviève Morneau-Vaillancourt; Sophie Aubé; Célia Matte-Gagné; Anne-Sophie Denault; Mara Brendgen; Simon Larose; Amélie Petitclerc; Isabelle Ouellet-Morin; René Carbonneau; Bei Feng; Jean Séguin; et al. (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0276532.].